Water-indexed benefits and impacts of California almonds. (January 2019) - Fulton, Julian; Norton, Michael; Shilling, Fraser
Highlights: The water footprint of one California almond has averaged 12 liters (3.2 gallons). Nutritionally and economically indexed water footprint indicators are proposed. Almonds are compared to alternative food and crop choices in California. Almond water footprints have large spatial and temporal variation in California. Proposed indicators can inform allocation decisions of scarce water resources. Abstract: California almonds have been the focus of recent media scrutiny because of the large amount of water required to grow individual nuts and, by extension, for the industry as a whole. With almond orchard acreage doubling in the last two decades and becoming California's most extensive irrigated crop, the questions arise: what are the benefits and impacts derived from this use of scarce water? Can we use this information to make decisions about growing and consuming this particular crop? We first use a water footprint approach to estimate total impact on water per unit of almond production in California, including variation in the water footprint over time (2004–2015) and across the production area. We then compare almonds to a set of other foods and crops grown in California using water footprint values and three other dimensions: nutritional value, per-unit-weight economic value, and total economic value. The water footprint of California almonds averaged 10, 240 liters per kilogram kernels (or, 12 liters per almond kernel), with substantial variation over the time period analyzed. Water footprint values also varied twofold across the production area, with the smallest water footprint being in the southern counties of California's Central Valley. In relation to dietary benefits, almonds were among the top three foods analyzed providing the greatest nutritional benefit per unit weights, however they had the highest water footprint value per unit weight. The direct economic benefits of almond production based on market sales were also greater than for any other major crop in California, however almonds again had the largest water footprint on a per-unit and aggregate basis. We find that nutritionally and economically indexed water footprint indicators provide information to better-inform discussions on the benefits and impacts of growing almonds using California's limited water resources, relative to other crops. Such composite indices can be used in combination with more local and contextual information on water availability/scarcity, existing impacts, and agricultural conditions to better optimize water use within single crops, such as the almond industry, and among crops within a region. We propose that this approach should be used to inform political- and value-weighted decisions about agricultural water allocation in California and beyond.